Tantangan dan Solusi Implementasi Pembelajaran Matematika Berbasis Digital Bagi Guru - Alpikar, Lendri; Putra, M. Rusni Eka; Episiasi, Episiasi (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the challenges and solutions in implementing digital-based mathematics learning for teachers at SD Negeri 36 Lubuklinggau and its alignment with the Merdeka Curriculum. The study employed a descriptive qualitative approach involving classroom teachers and mathematics teachers as research subjects. Data were collected through in-depth interviews, classroom observations, and documentation of teaching materials, and analyzed thematically through data reduction, data display, and conclusion drawing. The findings indicate that the main challenges faced by teachers include limited digital competence, inadequate infrastructure, and difficulties in designing interactive digital mathematics learning suited to elementary school students. Nevertheless, teachers have begun to integrate digital media and simple online learning platforms into mathematics instruction. Proposed solutions include strengthening teachers’ digital pedagogical competence based on the TPACK framework, optimizing school facilities, and developing student-centered digital learning strategies in line with the Merdeka Curriculum. This study is expected to contribute to improving the quality of digital-based mathematics learning in elementary schools. Keywords: Digital Learning, Mathematics Education, Elementary School Teachers, Merdeka Curriculum